Sustainable Leadership and Environment: An Empirical Study in Organizational Context - Saqib Hussain (NUST Journal of Social Sciences and Humanities)
Over the last three decades, the environment has become a hotly discussed topic all over the world. The United Nations has set up seventeen Sustainable Development Goals (SDGs) to achieve a standard of sustainable practices in the world including both developed and developing countries. Among these goals, the environment is regarded as a primary concern for all countries. The purpose of this research is to identify potential environmental indicators and challenges in organizational settings. This paper specifically investigates the impact of sustainable leadership on the environment, both directly and indirectly, through environmental practices and sustainable culture. Using a sample of 306 organizational personnel and Partial Least Square (PLS) Structural Equation Model (SEM), the results reveal that Sustainable Leadership (SL) have a significant impact on environmental sustainability. The results also indicate that Environmental Practices (EP) and Sustainable Culture (SC) influence Green Performance (GP). Findings of this study reinforce the organization’s concern for environmental sustainability and suggest how organizations and institutions can improve the environment through sustainable leadership. This is the first research to not only empirically study the interaction of SL and GP, but also to throw light on the existing literature by investigating the mediating function of environmental practices and sustainable culture and the underlying relationship.